Listeria meningitis with rapid progression of hydrocephalus: a case of a 16-month-old girl with febrile status epilepticus as the first symptom - Hye Min Kim; Jieun Lim; Joo Young Jeon; Ji Hye Kim; Il-Tae Hwang; Yoon Young Yi (Pediatric Emergency Medicine Journal, 2023)
Listeria monocytogenes is a rare cause of bacterial meningitis, particularly beyond the neonatal period. This article describes a 16-month-old girl who presented with a new-onset febrile status epilepticus, and subsequently developed altered mentality and lethargy. L. monocytogenes was detected on a point-of-care, multiplex polymerase chain reaction using the cerebrospinal fluid. On day 3, she developed a rapidly progressive hydrocephalus. Her consciousness improved after placement of an external ventricular drain. After 3-week antibiotic therapy, she was successfully discharged without residual complications.